2015
DOI: 10.1159/000434753
|View full text |Cite
|
Sign up to set email alerts
|

Stethoscope Hygiene: Practice and Attitude of Medical Students

Abstract: Objective: The purpose of this study was to evaluate the frequency and attitude of medical students towards cleaning their stethoscopes. Subjects and Methods: A cross-sectional study was carried out in the first week of December 2013. The study included 771 students (397 in their fourth and 374 in their sixth year) from the Faculty of Medicine, University of Belgrade, Serbia. An anonymous questionnaire was distributed to students before the start of compulsory lessons in classrooms. Results: 317 of the 397 fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
7
9
2
1
Order By: Relevance
“…In this study, it was found that healthcare providers who had a favorable attitude towards infection prevention were almost two times more likely to disinfect their stethoscope after very use than healthcare providers who had an unfavorable attitude. The current finding was in agreement with a study conducted by Gazibara et al [48], which reported a positive correlation between a higher frequency of stethoscope cleaning and stronger positive notion that a stethoscope should be cleaned.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, it was found that healthcare providers who had a favorable attitude towards infection prevention were almost two times more likely to disinfect their stethoscope after very use than healthcare providers who had an unfavorable attitude. The current finding was in agreement with a study conducted by Gazibara et al [48], which reported a positive correlation between a higher frequency of stethoscope cleaning and stronger positive notion that a stethoscope should be cleaned.…”
Section: Discussionsupporting
confidence: 94%
“…It was found that healthcare providers who had favorable attitude towards infection prevention were 1.73 times more likely to disinfect their stethoscope after very use than those healthcare providers who had unfavorable attitude. The current finding was in agreement with a study conducted by Gazibara et al [41], which reported a positive correlation between a higher frequency of stethoscope cleaning and the stronger positive notion that a stethoscope should be cleaned. In line with this finding a study conducted in Addis Ababa also reported a significant positive association between positive attitude towards infection prevention and good infection prevention practices [27].…”
Section: Discussionsupporting
confidence: 94%
“…However, the current finding was lower than the finding from Serbia, in which (80.8%) of the respondent clean their stethoscopes [41], and a study from French, reported (82%) of study participants clean their stethoscopes regularly or from time to time [42]. Additionally, the current finding was much lower than a study from Scotland, in which 78.6% of respondents clean their stethoscopes [43].…”
Section: Discussioncontrasting
confidence: 83%
“…The colony forming units (CFUs) obtained were noted and the bacterial isolates were identified by standard microbiology identification techniques [6]. The antimicrobial susceptibility pattern for the isolated strains was determined as per clinical laboratory standards institute (CLSI) guidelines and drug resistant bacteria like methicillin resistant Staphylocoocus aureus (MRSA), vancomycin resistance in gram positive cocci, extended spectrum β lactamase (ESBL) and metallo β lactamase (MBL) production in gram negative bacteria were also tested [7,8].…”
Section: Sample Collection and Processingmentioning
confidence: 99%